Non-invasive DNA extraction for molecular identification of royal Bengal tiger Panthera tigris tigris (Dhaka University Journal of Biological Sciences, 2021)
The flagship animal species of Sundarbans, the Royal Bengal tiger (Panthera tigris tigris) is under threat of extinction. Its natural population is declining day by day. So, to avoid killing and harming the animal, the use of non-invasive samples such as scat, hair, or scent is preferred for DNA extraction and subsequent genotyping of tiger species. DNA has been extracted from scat samples of the Bengal tiger in the present study, and a fragment of the cytochrome b gene has been sequenced after PCR with species-specific primers. DNA has been extracted manually using a previously described methodology with slight modifications. The size of the PCR product and sequence of cytochrome b gene indicates that tiger DNA is successfully extracted from scat samples using tigerspecific primers. Thus, presence of tiger DNA can be detected by using this method just by the PCR product size in the gel. This is the first report of a partial sequence of mitochondrial cytochrome b gene of P. t. tigris from Bangladesh.Dhaka Univ. J. Biol. Sci. 30(2): 325-330, 2021 (July)